If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 13 = -117 + -7x Reorder the terms: 13 + 6x = -117 + -7x Solving 13 + 6x = -117 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 13 + 6x + 7x = -117 + -7x + 7x Combine like terms: 6x + 7x = 13x 13 + 13x = -117 + -7x + 7x Combine like terms: -7x + 7x = 0 13 + 13x = -117 + 0 13 + 13x = -117 Add '-13' to each side of the equation. 13 + -13 + 13x = -117 + -13 Combine like terms: 13 + -13 = 0 0 + 13x = -117 + -13 13x = -117 + -13 Combine like terms: -117 + -13 = -130 13x = -130 Divide each side by '13'. x = -10 Simplifying x = -10
| 90-3x=3x+24 | | 14.9+2.6y=4.5 | | 5x+23=3x+65 | | 5-8x=43-22x | | 54-6x=3x+21 | | 126-4x=4x+22 | | -3y-7.8=-9.6 | | -3x-7.8=-9.6 | | 3x+17=11x+3 | | 2x+51=6x+45 | | 5x-22=38 | | 4y-2=6 | | 147-3x=33x+15 | | 1+87-g=g | | 2(5x-2)=4(2x+3) | | 4x-(x+2)=11x | | 7x+1-6x+x+2= | | 13x-(22-5x)=4(3x+5) | | (-5)*8= | | -65-2x=5-2x | | 6*(-8)= | | 176-3x=42x+21 | | 14-8x=50-15x | | 20x-10-[5(3x+1)-3(6x-5)]-5(6x+1)=0 | | 12-(-3)= | | 83-[9*(-3)]= | | 83-[9X(-3)]= | | 12*z= | | (a+2)(a+7)=0 | | 21w^2+35w=0 | | (-6)x(-4)x(-8)= | | 3a^2+18a=0 |